Effect of different coupling agents on the interfacial properties of tube–internally insulated foam materials interface in a composite cross‐arm under water environment. Issue 2 (3rd March 2021) - Liu, Yunpeng; Li, Le; Liu, Hechen; Li, Xiaolin; Liu, Donggen; Liu, Lei; Tang, Li; Zhou, Songsong
Abstract: In recent years, electrical breakdown accidents for composite cross‐arms in rain‐impacted environments have occurred which might be ascribed to the degradation of the tube–internally insulated foam materials interface. This research has focused on the different coupling agent treatments (KH‐550, KH‐560, KH‐792, and IPTS) of the tube–internally insulated foam materials interface. The effect of different coupling agents on the interfacial electrical and physical properties in a water environment have been studied. The leakage current and compressive shear strength of the interface were investigated after water diffusion pre‐stress. Three‐dimensional computed tomography ( μ CT) was used to study the interface cross‐section tomogram, interface three‐dimensional volume rendering, and relative interface porosity. The interfacial hydrolysis resistance ability and the interfacial strength modified by various coupling agents were effectively reflected by the compressive shear strength and relatively defect ratio. The results revealed the ranking of the comprehensive coupling effect was KH‐560>KH‐550>KH‐792>IPTS, which provides significant guidance for modifying internal insulation interface performance for composite cross‐arms.